The Effectiveness of Instructional Computer Program on Third Primary-Social Course-Students in Ma'an - Hani Obeidat; Khalid al-Atiat; Mustufa Jwaifell (My University, 2010)
This study aimed to examine an instructional computer program effect on third grade students' achievement, studying social course in Ma'an city as compare to traditional method. Therefore, a sample of 63 students was chosen from Dorar Bin Al-azwar School, divided into two equivalent groups, experimental group (32) and control group (31). The Pretest was used to measure the equivalence between the two groups by using The Independent-Sample (T-Test), testing reliability by Alpha (Cronbach) and its validity by referees. The developed Instructional Computer Program by the two researchers was used on the experimental group whereas the control group was left without any special procedures. ANKOVA was used to examine the hypothesis in order to measure the students' achievement apparent differences, where F(43.427) with degree of freedom(60), indicating significant differences under α(0.05), between the two groups' achievement in favor of the experimental group on a mean(17.41) and Std Deviation(2.76), which showed that The Instructional Computer Program had great effect on students' achievement.

هدفت هذه الدراسة التعرف الى أثر برنامج حاسوب تعليمي على تحصيل طلبة الصف الثالث الأساسي في مدينة معان لمادة التربية الاجتماعية والوطنية مقارنة بالطريقة الاعتيادية، حيث تم اختيار عينة مقصودة من طلبة الصف الثالث الأساسي من مدرسة ضرار بن الأزور موزعين على أربع شعب بواقع (63) طالباً، حيث تم تقسيمهم الى مجموعتين الأولى تجريبية بواقع (32) طالباً والثانية ضابطة بواقع (31) طالبا بموجب اختبار قبلي تم استخراج صدقه من خلال مجموعة محكمين وثباته من خلال معامل الاتساق الداخلي (كرونباخ ألفا) حيث تم فحص تكافؤ المجموعتين من خلال اختبار ت حيث كانت قيمة ت (0.619) بمستوى دلالة α (0.483)، وقد استخدم الباحثان في تدريس المجموعة التجريبية برنامج حاسوب تعليمي طوره الباحثان لهذا الغرض، بينما تم تدريس المجموعة الضابطة بالطريقة الاعتيادية، واخضعت المجموعتان الى اختبار بعدي لقياس تحصيلهم بعد المرور بالخبرة التعليمية، حيث تبين وجود فروق ظاهرية في التحصيل بين المجموعتين، ولفحص هذه الفروق تم استخدام تحليل التباين (ANCOVA) لمعرفة دلالة الفروق عند مستوى α (0.05) وضبط الأثر المصاحب حيث كانت قيمة ف (43.427) بدرجة حرية (60) وهذا يعني أنها دالة إحصائياً ولصالح المجموعة التجريبية بمتوسط (17.41) وبانحراف معياري (2.76) وتعزى هذه النتيجة إلى فاعلية برنامج الحاسوب التعليمي.
أثر استخدام برنامج حاسوب تعليمي على تحصيل الطلبة في مادة التربية الاجتماعية والوطنية للصف الثالث الأساسي في مديرية تربية معان